2011
DOI: 10.1377/hlthaff.2010.0526
|View full text |Cite
|
Sign up to set email alerts
|

How A Regional Collaborative Of Hospitals And Physicians In Michigan Cut Costs And Improved The Quality Of Care

Abstract: There is evidence that collaborations between hospitals and physicians in particular regions of the country have led to improvements in the quality of care. Even so, there have not been many of these collaborations. We review one, the Michigan regional collaborative improvement program, which was paid for by a large private insurer, has yielded improvements for a range of clinical conditions, and has reduced costs in several important areas. In general and vascular surgery alone, complications from surgery dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
163
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(163 citation statements)
references
References 28 publications
0
163
0
Order By: Relevance
“…The Blue Cross Blue Shield of Michigan Cardiovascular Consortium-PCI registry is a regional collaborative with an active focus on multicentric quality improvement and may or may not be representative of the wider population of patients undergoing PCI in the United States. 12 A proportion of patients had their infusion stopped before leaving the catheterization laboratory because of occurrence of bleeding complications in the catheterization laboratory, and we were not able to identify this from the registry data. Inclusion of these patients in the catheterization laboratory-only group would tend to negate the benefit of using such an approach and likely reduce the observed reduction in bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Blue Cross Blue Shield of Michigan Cardiovascular Consortium-PCI registry is a regional collaborative with an active focus on multicentric quality improvement and may or may not be representative of the wider population of patients undergoing PCI in the United States. 12 A proportion of patients had their infusion stopped before leaving the catheterization laboratory because of occurrence of bleeding complications in the catheterization laboratory, and we were not able to identify this from the registry data. Inclusion of these patients in the catheterization laboratory-only group would tend to negate the benefit of using such an approach and likely reduce the observed reduction in bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…The only study that tested this in a randomized fashion in patients undergoing contemporary PCI for stable and unstable coronary artery disease demonstrated no difference in ischemic events with use of an abbreviated infusion compared with the standard technique, while a reduction in bleeding events was noted. by guest on May 11, 2018 http://circinterventions.ahajournals.org/ Downloaded from described by investigators from the University of New York, SUNY Downstate Medical Center. 9 Finally in the largest series to date, Kini et al 25 described a reduction in bleeding and cost with the use of a bolus-only approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In adult surgical subspecialties, multicenter quality improvement collaboratives have proven to be successful models for sharing these types of best practices across hospitals, and reducing variation in clinical outcomes and costs. [31][32][33] A regional collaborative in Michigan is estimated to reduce complications after general and vascular surgery in ∼2500 patients each year, translating into annual savings of ∼$20 million. 31 New initiatives in the field of pediatric cardiology and cardiac surgery such as those sponsored by the Pediatric Heart Network and the Pediatric Cardiac Critical Care Consortium (PC 4 ) aim to employ similar approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported decreased morbidity and mortality rates, and decreased costs, associated with regional quality collaboratives. [32][33][34][35][36] There is no doubt surgical outcomes have improved over the last decade. Advances in operative technique, surgical checklists, performance-related payment, selective referral, and outcomes feedback have each contributed to these improvements in some way.…”
Section: Discussionmentioning
confidence: 99%